2008
DOI: 10.1186/1471-2458-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Finnish service screening programme on breast cancer rates

Abstract: Background: The aim of the current study was to examine impacts of the Finnish breast cancer (BC) screening programme on the population-based incidence and mortality rates. The programme has been historically targeted to a rather narrow age band, mainly women of ages 50-59 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 26 publications
6
51
0
Order By: Relevance
“…Most of the study population in Anttila et al 19 was included in Sarkeala et al 9 An overlap similar of that seen in Finland was found for the six Swedish publications, with the 13-area study 18 giving the best coverage of the Swedish data.…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…Most of the study population in Anttila et al 19 was included in Sarkeala et al 9 An overlap similar of that seen in Finland was found for the six Swedish publications, with the 13-area study 18 giving the best coverage of the Swedish data.…”
Section: Methodsmentioning
confidence: 69%
“…One study had an accrual period shorter than the follow-up period and used breast cancer cases from one age group and breast cancer deaths from an age group including older women. 19 This study reported a RR of 0.89. The studies with the most unbiased comparisons are those able to control for changes over time without introducing a healthy user bias and where the accrual period is similar to the follow-up time for breast cancer deaths (those in the top half of Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Mortality in this age group started to decline significantly already since 2000 -about four years before the start of organized screening. Considering that it takes about five years for incidence and mortality to become stable after screening [21], it is difficult to attribute the observed decrease in mortality to the impact of organized screening, although opportunistic screening can obscure the effect of organized screening [22]. It was shown previously that the proportion of localized cancers in age group 50-59 increased from 33% in 1995-1999 to 46% in 2000-2004.…”
Section: Discussionmentioning
confidence: 99%